MANTRA RITUAL GALUNGAN DALAM MASYARAKAT DUKUH WONOMULYO MAGETAN: KAJIAN SASTRA LISAN ALBERT B. LORD - , YUNITA FURINAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A ritual cannot be separated from the presence of mantra. Mantra as part of the culture, the culture has a close relationship with the owner of mantras. Ethnographic method that serves to explain the culture is fitting to discuss the mantra. as well as between one of the products of oral literature is always related how their orality. Orality according to Albert B. Lord covers how transmission, composition, formulas and themes which are owned by the oral poet before a performance. The creation process is begun by how Sudjito as an oral poet see and hear the oral object from a teacher. Furthermore, the composition process to arrange the theme and the formula was done. The formula was obtained from the teacher in the form of phrases or words that are repeated, while the theme is a main of the formula. That formula and theme was recomposed by Sudjito before doing the show. Through that formula, it was known that mantra in Galungan ritual had a special structure, while the theme was related with the public relation in Wonomulyo hamlet and the surrounding of microcosm and macrocosm